Osteocyte transition induced by quiescent vascular smooth muscle cells through paracrine signaling is independent of shear stress - Fernandes, Célio J.C. [UNESP]; van der Eerden, Bram C.J.; Silva, Rodrigo A. Foganholi; Fuhler, Gwenny M.; Peppelenbosch, Maikel P.; Zambuzzi, Willian F. [UNESP] (Elsevier, 2025)
We investigated how vascular smooth muscle cells (VSMCs) shape osteolineage fate under mechanosignaling, with emphasis on validating effects in mesenchymal stromal cells (MSCs), a more primitive stage than differentiated osteoblasts. Conditioned media from shear-stressed and non-stressed VSMCs challenged primary human osteoblasts and human MSCs for up to 28 days. Across both cell types, VSMCs robustly promoted osteoblast-to-osteocyte plasticity, evidenced by morphological remodeling and increased expression of osteocyte markers (GP38, SOST, DMP1, miR-23a, FGF23). Notably, non-stressed VSMC–conditioned medium elicited stronger osteocyte-function signatures, including a > 10-fold rise in RANKL transcripts, and these responses were recapitulated in MSCs, demonstrating that VSMC cues instruct osteogenic commitment at an earlier lineage stage and converge on an osteocyte-like phenotype. Mechanistically, small extracellular vesicles (sEVs) emerged as key mediators of VSMC–bone crosstalk: sEV cargo from non-stressed VSMCs displayed higher SOST and DMP1 transcripts, along with phosphor - β-catenin, phospho-connexin-43, and ATP, suggesting pathways that support osteocyte survival and function. Collectively, our data position VSMCs as pivotal instructors of osteolineage progression - from MSC commitment to osteocyte specification - via sEV-dependent communication, with non-stressed VSMCs exerting the strongest effect, particularly on functional readouts such as RANKL. Further, these findings support VSMC-sEV–inspired, cell-free approaches to modulate osteocytogenesis and regulate bone remodeling, while proposing SOST/DMP1/miR-23a as candidate circulating markers of osteocyte function and treatment response.